2014
DOI: 10.1016/j.biomaterials.2013.11.062
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a polyurethane-based reverse thermal gel on bone marrow stromal cell transplant survival and spinal cord repair

Abstract: Cell therapy for nervous tissue repair is limited by low transplant survival. We investigated the effects of a polyurethane-based reverse thermal gel, poly(ethylene glycol)-poly(serinol hexamethylene urethane) (ESHU) on bone marrow stromal cell (BMSC) transplant survival and repair using a rat model of spinal cord contusion. Transplantation of BMSCs in ESHU at three days post-contusion resulted in a 3.5-fold increase in BMSC survival at one week post-injury and a 66% increase in spared nervous tissue volume at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 51 publications
1
47
0
Order By: Relevance
“…The latter allowed enzymatic degradation of the hydrogel in the presence of cholesterol esterases. They showed, in a spinal cord contusion model, that transplantation of bone marrow stromal cells (BMSCs) in hydrogel enhanced cell survival and led to superior locomotor and sensory-motor recovery [68]. In another study, Jones et al reported the preparation of PEG hydrogels containing a collagenase-sensitive peptide, allowing for hydrogel degradation in the ECM microenvironment [69].…”
Section: Degradabilitymentioning
confidence: 97%
“…The latter allowed enzymatic degradation of the hydrogel in the presence of cholesterol esterases. They showed, in a spinal cord contusion model, that transplantation of bone marrow stromal cells (BMSCs) in hydrogel enhanced cell survival and led to superior locomotor and sensory-motor recovery [68]. In another study, Jones et al reported the preparation of PEG hydrogels containing a collagenase-sensitive peptide, allowing for hydrogel degradation in the ECM microenvironment [69].…”
Section: Degradabilitymentioning
confidence: 97%
“…Neutrophils and macrophages may also cause MSC death by the formation of reactive oxygen species that cause membrane damage leading to death. Indeed, transplanting the cells within a polyurethane-based biogel with antioxidative properties increases short term (one week) survival of MSCs [6]. Longer term (4 week) survival however, is unaffected by this gel, probably due to biodegradation of the gel.…”
Section: The Role Of the Immune System In Msc Transplant Survivalmentioning
confidence: 99%
“…Table 1 provides an overview of studies that have reported on bone marrow-derived MSC survival after transplantation into animal models of spinal cord injury. Studies that provide quantitative data on MSC survival after SCI report survival rates between 0 [14,15] and 52% [8] one week after transplantation and between 0 [6,[16][17][18][19][20] and 8% [21] one month after transplantation without survival enhancing therapies. In some cases, presence of MSCs up to two months [2,13,[22][23][24][25] and even three months [11,26,27] was reported after transplantation into models of spinal cord injury, but usually no or very few cells survive at these time points.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other investigators have used a variety of biomaterials in SCI as injectable, nonstructured delivery vehicles after partial lesions such as hemisection, [24][25][26][27][28][29] contusion, or compression injury. 30,31 These incomplete lesion models spare a degree of CNS tissue at the injury site, thus in these models it is difficult to differentiate between true regeneration and distal axonal sprouting or remodeling. The complete transection lesion followed by scaffold placement provides a model where regeneration can be studied functionally and anatomically and the local environment in and around the scaffold precisely controlled.…”
mentioning
confidence: 99%